Addressing Housing Challenges Faced by People with HIV in Ontario - McMaster Health Forum (My University, 2010)
Video interviews with participants in a stakeholder dialogue about Addressing Housing Challenges Faced by People with HIV in Ontario (on YouTube).
http://www.youtube.com/playlist?list=PL271398820A39D594&feature=plcp
Keywords: housing; HIV; Ontario